Retrospective analysis of diagnostics and treatment of acute hematogenous osteomyelitis in children based on clinical, anamnestic and microbiological characteristics - L. F. Pritulo (Zaporožskij Medicinskij Žurnal)
Clinical, anamnestic and microbiological parameters for last 10 years were studied in 110 children with an acute hematogenous osteomyelitis. It is shown, that major factors for occurrence of an acute hematogenous osteomyelitis in children are infl ammatory diseases of nasopharyngeal and dental-maxillary system, purulent diseases of skin and hypodermal layer, pneumonia and fl u infection, traumas of bones. During microbiological analysis it is established, that gram-positive microfl ora prevails at local and septic form, and gram-negative microfl ora - at toxic one. Presence of positive hemoculture and clinical signs in patients with septic and toxic forms at entering the hospital testifi es to presence of a septic infection and sepsis. Method of choice for treatment of an acute hematogenous osteomyelitis in children is osteoperforation with sanitation and drain of the marrow channel, and at presence of osteomyelitic phlegmonas - it is its opening and drainage in combination with anti-intoxication therapy, discrete plasmophoresis and immunotherapy.